Assessment of immunological techniques in the diagnosis and prognosis of ocular malignant melanoma. Issue 3 (March 1985) - Cochran, A. J.; Foulds, W. S.; Damato, B. E.; Trope, G. E.; Morrison, L.; Lee, W. R.
Abstract : Tests of cell mediated immunity (one and two stage leucocyte migration inhibition assays) and humoural immunity (membrane immunofluorescence and serum effects on leucocyte migration) were done with leucocytes and sera from 36 patients with uveal melanoma, five with conjunctival melanoma, 21 with non-malignant ocular disease, and 189 with cutaneous melanoma. Cell mediated reactivity with melanoma extracts and serum reactivity with cultured melanoma cells were significantly more frequent in the melanoma patients, but control donor reactivity was also relatively high. Maximum reactivity was found with cells or serum from those patients in whom, on pathological examination, the intraocular melanoma had penetrated the sclera and in patients with conjunctival melanoma. Maximum separation of melanoma patients from control donors was achieved by consideration of the results of several tests done simultaneously. These immunopathological studies were made during the period from 1972 to 1978. At follow-up in 1983 four of the five patients suffering from conjunctival melanoma had died from metastases, and 10 of the 36 with uveal melanoma had died from metastatic disease. The immunological reactions, while of some value in separating melanoma patients from those without melanoma, did not predict whether a particular patient with uveal melanoma would die of metastatic disease or would survive.